Impact of Stakeholders Interest on Firm Financial Performance with Mediating Role of Financial Decision (Journal of Asian Development Studies, 2024)
The study explored the impact of stakeholders' interests on firm financial performance and the mediating role of a firm's financial decisions. The study has included all the banks as the population of the study. One hundred twenty-eight banks operate in the Pakistani market, which is the study population and secondary data was collected from 75 banks from 2012 to 2021. The study used the GMM model as the analysis model. The correlation model showed that the highest correlation value was found for ROE, with 0.56. The findings of the Hausman Test showed that the Hausman test for both ROA and ROE supports FE for estimating results. The next test after the recommendation of FE is to check whether to include the fixed effect (FE) or pooled OLS model. The findings of the Bruesch Pagan test for both ROA and ROE have been significant, meaning that the FE model should be used to estimate results. The Autoregressive Model of Endogeneity findings showed that the ROA and ROE have a significant relationship with L.ROA (0.469; 0.642 and L.ROE 0.412; 0.489) and show a positive sign of the endogeneity problem. The findings of the GMM model reported a significant and positive relationship between ROA and a significant but negative relationship was received for ROE in GMM. In contrast, FE has reported a positive relationship. This study encourages future research to extend the study across different industries by examining the phenomenon as a time series analysis, thereby detecting insightful knowledge of the relationship's development